Russia’s youth non-commercial organizations: Identity politics and the collective “I” - G. F. Gabdrahmanova; R. D. Galiullin (RUDN journal of Sociology)
The last decade in Russia is characterized by the formation of the institutional public activism, which is expressed in the emergence of its new, legislative form - socially oriented noncommercial activity. The article aims at examining the foundations of the group identity of the youth in such socially oriented non-commercial (non-governmental) organizations (SONGOs) and at identifying those significant social ideas that underlie the identity of the Russian youth. The study is based on the concept of identity, interpreting the ideas of youth movements, and on the resource mobilization model which allows us to study the collective “I” of the youth SONGOs. This methodological framework presents the Russian youth’s activism as a multi-level system of collective action. The empirical base of the study consisted of the following: a list of applications submitted by SONGOs to the Presidential Grant Foundation for financial support in 2017-2023; interviews with leaders of youth organizations in the Republic of Tatarstan; participant observation at the opening and closing ceremonies of summer camps of two youth associations; the authors’ survey of the youth in the Republic of Tatarstan and surveys of the Russian youth conducted by WCIOM and Levada Center (1). As the results of the study showed, the agenda of SONGOs focuses on social (in terms of socialization), local and national-civil identity of the younger generation. Thus, despite different tasks of youth organizations, a clear association with Russia is traced in all their significant events through state symbols and leaders’ speeches. Social activists are ready to improve their competencies in certain professions and participate in the formation of a pool of young activists as a separate professional group with the relevant knowledge and skills. The basis of the group identity of youth SONGOs is their self-perception as an intermediary between the authorities and the younger generation, capable of identifying, actualizing and developing diverse interests of the youth. The further influence of SONGOs on the youth socialization and identity will be largely determined by the attitude of the Russian population to the new type of social activism.